Comparative Advantage in Tourism - A Supply-Side Analysis of Tourism Flows - Jie Zhang; Camilla Jensen (European Regional Science Association (ERSA), 2005)
The purpose of the paper is to relate the tourism demand model with the traditional theories that explain international trade flows. In the existing tourism literature, tourism flows and tourism demand forecasts are typically explained by the demand-side variables. But in the traditional trade theories, international trade flows are explained from the supply-side variables, i.e. the comparative advantage of the exporting countries. A model is proposed in the paper, trying to explain in a modern and global economy, the factors that from a supply-side perspective can decide the comparative advantage of countries in a certain type of service activity. The preliminary results render a strong support for the relevance of certain supply-side factors in explaining international tourism flows such as both natural endowments and created assets associated with foreign investments, hotel capacity and level of development.
Keywords: 330